The Tropospheric Pathway of the ENSO-North Atlantic Teleconnection - Jiménez Esteve, Bernat; id_orcid:0 000-0003-2706-5309; Domeisen, Daniela; id_orcid:0 000-0002-1463-929X (American Meteorological Society, 2018)
ISSN:0894-8755 ISSN:1520-0442